Differences in strength, flexibility and stability in freestyle and Greco-Roman wrestlers - Basar, S.; Duzgun, I.; Guzel, N. A.; Cicioglu, I.; Celik, B. (Journal of Back and Musculoskeletal Rehabilitation, 2014)
Wrestling includes a variety of functional properties: muscular strength, flexibility, neuromuscular coordination, and static and dynamic balance. The aim of the study was to identify differences in the strength, flexibility, postural stability and core stabilization of young national and international wrestlers in different weight groups. Eighty-one male wrestlers (17-21 years old) were divided into 6 groups according to their body mass (light, middle and heavy) and wrestling style. The lumbosacral flexion, extension and lateral flexion range of motion, hamstring extensibility, back and leg muscle strength, postural stability, and core stabilization were assessed. Greco-Roman wrestlers had a higher lean body mass (6-12%) compared with freestyle wrestlers. However, the trunk lateral flexion flexibility was better in the Greco-Roman wrestlers (6-7%) than in the freestyle wrestlers, and the absolute back strength (BS) and leg strength (LS) were similar for both styles of wrestling. The BS/LBM and LS/LBM in the freestyle wrestlers were greater than in the Greco-Roman wrestlers, and the Light weight Greco-Roman wrestlers had the highest BS/LBM. The heavy weight Greco-Roman wrestlers and the light weight freestyle wrestlers had the greatest LS/LBM values. The postural control was similar for the two styles of wrestlers; however, the heavy weight Greco-Roman wrestlers had greater postural control in all directions compared with the light and middle weight Greco-Roman wrestlers. The core stabilization did not differ for the Greco-Roman and freestyle wrestlers except in the lateral bridge. The style of wrestling demonstrates different strength, flexibility and stability demands on the body. The differences between Greco-Roman and freestyle wrestlers may be due to the wrestling style differences in training and to competition-related demands.